Features of Green Organisational Culture in Utena District Municipality: Implications for Social Welfare - Strautnikienė, Sigita; Toleikienė, Rita (Social Welfare: Interdisciplinary Approach, 2026)
Sustainable development goals, social responsibility, the Green Deal and climate neutrality increasingly encourage local government institutions to reconsider their principles, values and modes of operation. Green organisational culture (hereinafter – GOC) is a multidimensional construct integrating value-based orientations with organisational practices, functioning as a strategic intangible resource. It enhances the capacity of local government to address environmental challenges, implement green initiatives, and support sustainable development. The study identifies four core GOC features – value-based, structural, behavioural, and symbolic – that collectively embed environmental principles into local government. These features facilitate not only environmental protection but also broader social welfare outcomes by promoting transparency, accountability, stakeholder participation, and policy continuity. Two dimensions of green public administration (hereinafter – GPA) are analysed: the transformation of internal organisational activities and management in line with sustainability principles, and the role of local government institutions in formulating, implementing and enforcing environmental and sustainability policies that affect citizens’ well-being. The analysis reveals that GOC functions as an intangible resource and organisational capacity necessary for the effective implementation of GPA and the pursuit of long-term social welfare goals. The research applies a qualitative case study methodology, focusing on Utena District Municipality as a single, embedded case. The research is based on triangulation, combining both qualitative and quantitative content analysis. A total of 31 municipal documents from the period 2020–2024 are analysed in order to ensure a comprehensive and reliable assessment of the phenomenon. Within the scope of this case study, the municipality is conceptualised as a unified organisational entity, integrating both the political level (the municipal council) and the administrative level (executive bodies). The case study of Utena District Municipality demonstrates a mature, proactive green culture. This is evident in the systematic integration of green values into decision-making, continuity of the green agenda, openness to innovation, and stakeholder empowerment. The findings demonstrate that GOC contributes to social welfare by improving the quality of life, fostering inclusive and transparent governance, and strengthening long-term sustainability-oriented decision-making at the local government level. The results highlight GOC as a mediating mechanism that translates environmental governance into tangible social and institutional benefits, thus confirming its role as a strategic capability in GPA.
Keywords: green organisational culture; green public management; local government institutions; sustainability; social welfare